Playing horror : narrative and genre in Valve's Left 4 Dead Series - Schäfer, Iris (2013)
The place of story and narrative in digital games has been a hotly contested topic within the field of Game Studies during the past two decades. Beyond the question of whether games can or should be used for telling stories, research interest has focused on the nature of game narratives and their distinct qualities in comparison to other expressive media, like literature and film. The aim of this thesis is to contribute to this debate by examining the elements involved in storytelling not in digital games overall, but in one particular series, namely Valve Software‘s Left 4 Dead and Left 4 Dead 2. The use of this in-depth case study allows an examination of how various different elements contribute to the series‘ particular horror narrative and story as opposed to delineating how one specific element can function in a variety of game fictions. The elements considered consist both of those borrowed or adopted from other expressive media, as well as some specific to game fictions and identified in previous research in the field. With the particular subject of horror game fiction and an additional theoretical background of horror fictions it is possible to examine how these various narrative constituents can be used for a specific narrative purpose, namely the conveyance of events in a threatening and horrific atmosphere. As a result, this thesis offers a concrete example of how diverse aspects of a game contribute in an interrelated and tightly interdependent way to the creation of game narrative and story.